Reach for the Skai : how to inspire, empower, and clapback - Jackson, Skai (A Yearling Book, 2021)
African American actress and activist Skai Jackson reflects on her rise to fame as a Disney Channel star and her role today as a modern Instagram influencer. She also provides advice on self-acceptance, empowerment, positivity, and bullying. Features dozens of color photographs throughout.